Hear the wind sing and Pinball,1973 - Murakami, Haruki
Lets you follow the fortunes of the narrator and his friend, known only by his nickname, the Rat. In this book, the narrator is home from college on his summer break. He spends his time drinking beer and smoking in J's Bar with the Rat, listening to the radio, thinking about writing and the women he has slept with, and more The narrator finds himself haunted by memories of his own doomed relationship but also, more bizarrely, by his short-lived obsession with playing pinball in J's Bar.